Injectable self-healing nano composite hydrogel as well as preparation method and application thereof
By using nanocomposite hydrogels that encapsulate quercetin bionic nanoparticles on diabetic wounds, the problem of slow healing in diabetic wounds is solved, and effective regulation and efficient healing of the wound microenvironment is achieved.
Patent Information
- Application Number
- CN202411788420.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-25
AI Technical Summary
The inflammatory microenvironment of diabetic wounds is difficult to effectively regulate, resulting in slow healing. The existing treatment methods have disadvantages such as low efficiency, high complexity and immune rejection.
The injectable self-healing nanocomposite hydrogel consisting of hyaluronic acid, oxidized hyaluronic acid and propargyl cysteine encapsulating quercetin bionic nanoparticles is achieved through differentiated delivery of nanoparticles and hydrogel matrix to effectively regulate the wound microenvironment.
This nanocomposite hydrogel can effectively clean inflammatory factors and reactive oxygen species in wounds, promote skin tissue remodeling, vascular repair and hair follicle regeneration, and significantly improve the healing efficiency of diabetic wounds.
Smart Images

Figure CN119679697A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and particularly relates to an injectable self-healing nanocomposite hydrogel and a preparation method thereof, wherein the injectable nanocomposite hydrogel has the properties of short gelation time, injectability, biodegradability, and drug sustained release, and provides a new clinical solution for drug administration of diabetic wounds. Background Art
[0002] The blood glucose concentration of diabetic wounds is high and they are susceptible to infection. The body's immune system disorder causes persistent inflammation and oxidative stress damage. In addition, vascular lesions lead to tissue hypoxia and insufficient nutrient delivery. The wounds are difficult to heal, seriously affecting the quality of life of patients and even leading to serious consequences such as limb ulceration and amputation. At present, the main methods for clinical treatment of diabetic wounds are through medical treatment, covering with gauze and other dressings, surgical debridement, ozone chemical debridement, etc. However, these methods have disadvantages such as low treatment efficiency, complex clinical treatment, and immune rejection. Therefore, it is urgent to develop new treatment methods to fully regulate the microenvironment of diabetic wounds and effectively promote wound healing.
[0003] Quercetin is a polyphenolic flavonoid substance that exists in a variety of natural plants and has a variety of biological activities, including antioxidant, anti-inflammatory and antibacterial effects. Quercetin is beneficial to blood sugar control and can effectively prevent and improve diabetic complications, including diabetic wounds, diabetic nephropathy, retinopathy, etc. Quercetin can effectively reduce the concentration of peroxides in tissues and protect tissues from oxidative damage. Quercetin has anti-inflammatory effects, can inhibit the production of proinflammatory cytokines, and reduce the expression of cyclooxygenase and lipoxygenase. At the same time, as a broad-spectrum antibacterial substance, quercetin can be used to prevent and treat a variety of bacterial infectious diseases. Therefore, quercetin shows good clinical application prospects in the field of diabetic wound repair. However, the structure of quercetin leads to its poor water solubility and low bioavailability, which hinders the widespread clinical application of quercetin. Nanoparticle encapsulation can effectively release drugs, improve bioavailability, have low immunogenicity, and be safe and non-toxic. Nanoparticles wrapped in cell membranes can not only reduce the recognition and phagocytosis of the endothelial system, but also actively target inflammatory cells through adhesion molecules on the surface of neutrophil membranes, further enhancing the therapeutic effect of quercetin.
[0004] Propargyl cysteine (SPRC) is a new type of endogenous hydrogen sulfide donor obtained by structural modification. It can regulate the level of hydrogen sulfide in the body, and protect myocardial ischemia and promote angiogenesis by exerting anti-inflammatory, antioxidant, and anti-fibrosis mechanisms. Modifying SPRC to oxidized hyaluronic acid through Schiff base bonds can release the regulation of the wound microenvironment and achieve pH-responsive release of hydrogen sulfide, thereby giving the hydrogel the effects of promoting angiogenesis and inhibiting scar formation. At the same time, hyaluronic acid can also promote epidermal proliferation and differentiation, scavenge oxygen free radicals, and promote the regeneration of damaged skin.
[0005] In summary, the present invention intends to combine cell bionic nanotechnology and hyaluronic acid hydrogel to construct a nanocomposite hydrogel with environmental interactivity, and differentially deliver different pharmacologically active drugs through nanoparticles and hydrogel matrix. The bionic nanocomposite hydrogel is expected to make full use of the synergistic gain effect of each component, effectively clean harmful factors such as inflammatory factors and reactive oxygen species in the wound microenvironment, induce skin tissue remodeling, promote vascular repair and hair follicle regeneration, and restore the normal function of the immune system, ultimately achieving the purpose of efficiently treating diabetic wounds. Summary of the invention
[0006] To solve the above technical problems, the present invention provides a method for preparing an injectable self-healing nanocomposite hydrogel and its application in diabetic wound repair, which improves the inflammatory microenvironment of diabetic wounds and accelerates wound healing by combining functional nanomaterials with gel scaffolds.
[0007] An injectable self-healing nanocomposite hydrogel is composed of hyaluronic acid, oxidized hyaluronic acid and propargyl cysteine encapsulating quercetin bionic nanoparticles. The hyaluronic acid, oxidized hyaluronic acid and propargyl cysteine are dissolved in a sodium hydroxide solution by physical blending to form a hydrogel solution. At the same time, gluconolactone and bionic nanoparticles are added and physically blended at room temperature to form a nanocomposite hydrogel. The quercetin encapsulating bionic nanoparticles are composed of quercetin encapsulating nanoparticles and activated neutrophils. The nanoparticles are prepared by a solvent evaporation method. The nanoparticles and neutrophils are encapsulated in an outer membrane by an ultrasonic probe.
[0008] Preferably, the nanoparticles and the neutrophil membrane are membrane-fused by an ultrasonic probe, and the mass ratio thereof is 5:1 to 1:5; the mass fraction of the hyaluronic acid is 8%-24%, the mass fraction of the oxidized hyaluronic acid is 8% to 12%, the mass fraction of the propargyl cysteine is 0.5% to 5%, and the drug is a hydrophilic hydrogen sulfide donor.
[0009] Preferably, hyaluronic acid, oxidized hyaluronic acid and propargyl cysteine are dissolved in a 1% by mass sodium hydroxide solution by physical blending.
[0010] Preferably, the neutrophils are obtained by DMSO-induced differentiation of the HL-60 cell line, and after further inflammatory stimulation, the inflammatory cytokine receptors and related adhesion factors are overexpressed on the cell surface after activation; the neutrophil membrane is obtained by mechanical grinding and differential centrifugation extraction, and the cell membrane vesicles are obtained by ultrasonic treatment.
[0011] Preferably, the relevant adhesion factors include membrane proteins such as CD11b, TNF-α, IL-1β, TLR-1, and TLR-2.
[0012] Preferably, the injectable self-healing nanocomposite hydrogel is prepared from raw materials in the following weight ratio: the mass fraction of the hyaluronic acid is 8-24%; the mass fraction of the oxidized hyaluronic acid is 8-12%; the drug used is propargyl cysteine, and the mass fraction of the drug is 0.5%-5%; the encapsulated quercetin bionic nanoparticles are PLGA bionic nanoparticles encapsulating quercetin, and the mass fraction of the encapsulated quercetin bionic nanoparticles is 0.5%-5%.
[0013] A method for preparing an injectable self-healing nanocomposite hydrogel is obtained by the following steps:
[0014] Preparation of encapsulated quercetin biomimetic nanoparticles: Encapsulated quercetin biomimetic nanoparticles are composed of quercetin encapsulated nanoparticles and activated neutrophils, and the nanoparticles are prepared by a solvent evaporation method; weigh the prescribed amount of PLGA and quercetin, dissolve them in an appropriate amount of organic solvent, add the organic solvent dropwise into a 10% polyvinyl alcohol aqueous solution, place the emulsion under probe ultrasound for an appropriate time and frequency, place it in a fume hood to remove the organic solvent, and then centrifuge the solution at an appropriate speed for 15 to 30 minutes to obtain drug-loaded nanoparticles, and then wash away the residual polyvinyl alcohol and free drugs through multiple same centrifugation conditions to obtain encapsulated quercetin nanoparticles; the nanoparticles and neutrophils are encapsulated by an ultrasonic probe to obtain encapsulated quercetin biomimetic nanoparticles.
[0015] Preparation of injectable self-healing nanocomposite hydrogel: Step 1, dissolving an appropriate amount of 8% to 24% hyaluronic acid and 8% to 12% oxidized hyaluronic acid in a 1%wt sodium hydroxide solution to prepare a mixed hyaluronic acid and oxidized hyaluronic acid solution with a mass fraction of 16% to 36%, and dissolving an appropriate amount of propargyl cysteine in the hyaluronic acid and oxidized hyaluronic acid solution to form a drug-loaded gel solution;
[0016] Step 2: adding an appropriate amount of gluconolactone to the gel liquid, and adding an appropriate amount of bionic nanoparticles at the same time, reacting for 30 seconds to 3 minutes under stirring at room temperature to obtain an injectable self-healing nanocomposite hydrogel.
[0017] Preferably, the mass fraction of the hyaluronic acid is 8-24%, the mass fraction of the oxidized hyaluronic acid is 8-12%, the drug used is propargyl cysteine, and the mass fraction of the drug is 0.5-2.5%; the nanoparticles are PLGA biomimetic nanoparticles encapsulating quercetin, and the mass fraction of the nanoparticles is 0.5-2.5%; the average particle size of the nanoparticles is 150-220nm, and the size of the nanoparticles encapsulating the neutrophil membrane is 170-240nm; the molecular weight of hyaluronic acid and oxidized hyaluronic acid is 800,000-150,0000Da; the mass fraction of the drug-loaded nanoparticles and the drug is 0.5-5%.
[0018] Preferably, the polymer used to prepare the quercetin encapsulated biomimetic nanoparticles is PLGA, a polylactic acid-glycolic acid copolymer (lactic acid: glycolic acid 75:25), with a molecular weight of 44,000 to 100,000 Da; the organic solvent used is a mixture of dichloromethane and acetone; the ratio of the organic solvent to the aqueous solvent is 1:2 to 1:9, and the ultrasonic probe frequency is 130 w, 60 s to 200 s.
[0019] Injectable self-healing nanocomposite hydrogels are used in the preparation of drugs for treating diabetic wounds.
[0020] The present invention uses PLGA polymer as a raw material to prepare nanoparticles as the core and encapsulate quercetin, and after HL-60 cells are induced to differentiate into neutrophils by DMSO, TNF-α stimulation is given, the cell membrane encapsulated nanoparticles are extracted, and a neutrophil membrane-encapsulated bionic nanoparticle drug delivery system is constructed. Hyaluronic acid and oxidized hyaluronic acid are used as raw materials to prepare an injectable self-healing hydrogel, and propargyl cysteine is modified in the hydrogel to construct a pH-responsive hydrogel drug delivery system. At the same time, the bionic nanoparticles are encapsulated in the hydrogel to obtain an injectable self-healing nanocomposite hydrogel. The bionic nanoparticle drug delivery system can not only use the surface molecules of the neutrophil membrane to increase the biocompatibility of the system, reduce the phagocytosis of the endothelial system, and adsorb inflammatory factors to play an inflammation neutralizing effect, but also use the inherent immune receptors on the cell membrane surface to achieve antibacterial effects, and can also use neutrophils to actively tend to endothelial cells to target wound inflammation sites, and deliver anti-inflammatory and antioxidant drug active ingredients to wound inflammation sites, while playing the role of nanoparticle sustained-release drugs and prolonging the drug action time.
[0021] At the same time, hyaluronic acid and oxidized hyaluronic acid can promote epidermal proliferation and differentiation, eliminate the effects of oxygen free radicals, and promote the regeneration of damaged skin. Oxidized hyaluronic acid and propargyl cysteine modified to the gel can quickly release drugs under the stimulation of the wound microenvironment, and deliver the active ingredients of the angiogenesis-promoting drug to the wound site. The gel slow-release nanoparticles and drugs play a role, prolonging the drug action time and reducing the frequency of gel replacement.
[0022] In the present invention, the neutrophil membrane is obtained by mechanically grinding HL-60 cells, giving them inflammatory stimulation after DMSO-induced differentiation, overexpressing related adhesion molecules on their cell membrane surfaces, and extracting them using differential centrifugation.
[0023] Compared with the prior art, the present invention has the following advantages and effects:
[0024] (1) The method for preparing an injectable self-healing hydrogel of the present invention is simple and quick to operate. The gel system can use different drugs, growth factors, nanoparticles, and liposomes according to different uses. The prepared drug-loaded gel can be injected in situ into the wound site and has good biocompatibility and biodegradability.
[0025] (2) The bionic nanoparticles of the present invention have multiple functions, which can effectively reduce the expression of inflammatory factors in the wound site, resist oxidation, and promote epidermal growth and collagen deposition.
[0026] (3) The propargyl cysteine of the present invention can effectively promote angiogenesis and promote the healing of diabetic wounds.
[0027] (4) The injectable self-healing nanocomposite hydrogel prepared by the present invention can be continuously applied to the wound surface to reduce the frequency of dressing changes. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a characterization diagram of the particle size and potential of the cell membrane and nanoparticles in the present invention, in which A and B are the average particle size and Zeta potential of the nanoparticles and the biomimetic liposomes encapsulated by the neutrophil membrane, respectively.
[0029] Figure 2 It is the encapsulation efficiency of quercetin by the nanoparticles in the present invention.
[0030] Figure 3 Transmission electron microscopy images of blank nanoparticles and biomimetic nanoparticle drug delivery systems in the present invention.
[0031] Figure 4 This is the qualitative detection result of the adhesion molecules on the surface of the nano drug delivery system of the present invention.
[0032] Figure 5 Scanning electron micrographs of the blank hydrogel (left) and the nanocomposite hydrogel (right) in the present invention.
[0033] Figure 6 This is a diagram showing the injectable self-healing performance of the nanocomposite hydrogel in the present invention.
[0034] Figure 7 This is a diagram showing the effect of promoting epithelial cell migration in the nanocomposite hydrogel system of the present invention, wherein: Figure 7 A is an optical microscope photo of cell migration. Figure 7 B is the healing curve, Figure 7 C is the healing rate after 12 hours.
[0035] Figure 8 This is a diagram showing the effect of promoting angiogenesis in the nanocomposite hydrogel system of the present invention, wherein: Figure 8 A is an optical microscope photo of blood vessel formation. Figure 8 B is a statistical diagram of branch points.
[0036] Fig. 9 9A is a diagram showing the therapeutic effect of the present invention on diabetic rats, 9A is a diagram showing wound healing at different time points, and 9B is a wound healing curve. DETAILED DESCRIPTION
[0037] In order to make the technical solution of the present invention easier to understand, the technical solution of the present invention is now clearly and completely described in the form of specific embodiments in conjunction with the accompanying drawings.
[0038] Example 1
[0039] Extraction and preparation of neutrophil membranes:
[0040] HL-60 cells were passaged and expanded with IMDM medium + 20% FBS + 1% PS in a cell culture incubator at 37°C, 5% CO2. 1% DMSO was added to the cell culture medium to induce cell differentiation and 10ng / ml TNF-α was given to stimulate the cells for 72h. The cells were centrifuged at 1000rpm / min for 5min to remove the supernatant and washed three times with PBS at 4°C, 1000rpm / min, and 5min. Use prepared membrane extraction buffer, the weight composition of the buffer is: 225mM mannitol, 75mM sucrose, 0.5% BSA, 0.5mM EDTA, 30mM Tris-HCl, 1% protease inhibitor; resuspend the cells, mechanically homogenize on ice, centrifuge, the temperature is controlled at 4°C, the weight is 800g, the time is 10min, remove the cell nucleus and other structures, centrifuge the supernatant again, the temperature is 4°C, the weight is 10000g, the time is 20min, remove the mitochondria and other structures, centrifuge the supernatant, the temperature is 4°C, the weight is 100000g, the time is 60min, resuspend the cell membrane with distilled water after centrifugation, freeze-dry and store at -80°C for later use.
[0041] Example 2
[0042] Preparation of PLGA nanoparticles:
[0043] According to PLGA (polylactic acid-glycolic acid copolymer, lactic acid: glycolic acid 75:25), the molecular weight is: 44,000~100,000Da, and 5~25mg is dissolved in 2ml of dichloromethane. The preferred prescription is 25mg PLGA (molecular weight: 75,000Da) dissolved in 2ml of dichloromethane. At the same time, prepare 10% polyvinyl alcohol aqueous solution. According to the solvent evaporation method: dichloromethane is added dropwise to 10% polyvinyl alcohol aqueous solution in a ratio of 1:2~1:7 to form uniform emulsion droplets, and the preferred ratio is 1:7. The emulsion is placed in an ultrasonic probe, and the probe frequency and time are: 130w, 60s~200s, and the preferred time is 160s. Ultrasonicate the emulsion until it is evenly dispersed, place it in a fume hood, place the glass bottle containing the emulsion on a magnetic stirrer at 800 rpm, rotate for 4 hours to evaporate the dichloromethane, place the emulsion in a centrifuge at 4°C and 15,000 rpm for 30 minutes, discard the supernatant and add ultrapure water to centrifuge three times to remove the polyvinyl alcohol to obtain nanoparticles. The average particle size of the nanoparticles is 180 nm as measured by a particle size analyzer. The zeta potential results are shown in Figure 1 .
[0044] Example 3
[0045] Preparation of quercetin nanoparticles:
[0046] According to polylactic acid-glycolic acid copolymer (lactic acid: glycolic acid 75:25), the molecular weight is: 44,000-100,000Da, 5-25mg of PLGA is dissolved in 1.5ml of dichloromethane, and 1-4mg of quercetin is dissolved in 0.5ml of acetone. The preferred prescription is 25mg PLGA (molecular weight: 75,000Da) dissolved in 1.5ml of dichloromethane, and 4mg of quercetin dissolved in 0.5ml of acetone. At the same time, a 10% polyvinyl alcohol aqueous solution is prepared. According to the solvent evaporation method: dichloromethane and acetone mixed organic solvent are added dropwise to a 10% polyvinyl alcohol aqueous solution in a ratio of 1:2 to 1:7 to form uniform emulsion droplets, preferably 1:7. The emulsion is placed in an ultrasonic probe with a probe frequency of 130w, 60s to 200s, and a preferred time of 160s. , ultrasonic to emulsion, placed in a fume hood, placed the glass bottle containing the emulsion on a magnetic stirrer at 800rpm, rotated for 4 hours to evaporate dichloromethane and acetone, placed the emulsion in a centrifuge at 4°C, 15,000rpm, for 30 minutes, discarded the supernatant and added ultrapure water for centrifugation three times to remove unencapsulated free drugs and polyvinyl alcohol to obtain quercetin nanoparticles. Take 100μl of quercetin nanoparticle solution and dissolve it in DMSO, and the encapsulated quercetin is determined by UV spectrophotometer according to the formula:
[0047] Encapsulation efficiency = (total quercetin - free quercetin) / total quercetin × 100%
[0048] Drug loading rate = (total quercetin - free quercetin) / nanoparticles × 100%
[0049] Calculate the encapsulation efficiency of quercetin, and we can see Figure 2 The encapsulation efficiency and drug loading of PLGA nanoparticles for quercetin are mainly affected by the molecular weight of PLGA and the dosage. According to the experimental results, the encapsulation efficiency and drug loading of PLGA with a molecular weight of 44,000Da are 75% and 10%. The nanoparticles prepared by PLGA with a molecular weight of 100,000Da have too large particle size and uneven particle size distribution, while the nanoparticles prepared by PLGA with a molecular weight of 75,000Da have a particle size of 180nm and an encapsulation efficiency and drug loading of 80% and 13%. Therefore, the best drug loading rate, encapsulation rate and stable and uniform particle size nanoparticles were selected, with a molecular weight of 75,000Da and 25mg PLGA encapsulating 4mg of quercetin.
[0050] Example 4
[0051] Preparation of neutrophil membrane-encapsulated biomimetic nanoparticle drug delivery system:
[0052] After the cell membrane is mixed with blank nanoparticles or quercetin nanoparticles at a ratio of 5:1 to 1:5, the preferred ratio is 1:1. Ultrasonic probe, probe frequency: 100w, 15s to 45s, super 1s, stop 1s, the optimal time is 30s, super 1s, stop 1s. Taking the optimal prescription as an example, a uniform neutrophil membrane-encapsulated biomimetic nanoparticle drug delivery system is obtained according to 1:1, such as Figure 1 The average particle size of the nanoparticles was 200nm as measured by a particle size analyzer. The cell membrane and nanoparticles were mixed and coated in the above steps at a mass ratio of 5:1 to 1:5. The coating ratio of 5:1 was not much different from that of 1:1, and the ratio of 1:5 did not change significantly from that of the nanoparticles without coating due to the low content of cell membrane. Taking the stability, uniformity and cell uptake of the nanoparticles into consideration, the preferred ratio was 1:1. Taking the ratio of 1:1 as an example, the morphology was characterized by transmission electron microscopy. Figure 3 It can be observed that the biomimetic nanoparticles have a regular spherical structure, uniform size, and a particle size of about 200 nm. Blank nanoparticles, neutrophil cell membranes, and biomimetic nanoparticles were subjected to gel electrophoresis and stained with Coomassie brilliant blue. Figure 4 It can be observed that the biomimetic nanoparticle drug delivery system has related proteins consistent with the neutrophil membrane.
[0053] Example 5
[0054] Preparation of injectable hydrogels:
[0055] Weigh 8% to 24% hyaluronic acid, 8% to 12% oxidized hyaluronic acid and 0.5% to 5% propargyl cysteine by mass fraction, dissolve in 1% mass fraction sodium hydroxide solution to form a gel solution. Weigh gluconolactone according to the molar ratio of sodium hydroxide to gluconolactone of 1:1, add it to the gel solution and stir at room temperature for 30s to 3min to obtain an injectable gel. Among them, the gelation time of weighing the prescription mass fraction of 8% hyaluronic acid, 8% oxidized hyaluronic acid and 0.5% propargyl cysteine is 3min. The gelation time of the gel of the prescription of 24% mass fraction hyaluronic acid, 12% oxidized hyaluronic acid and 5% propargyl cysteine is 30s. At the same time, the gelation time of the prescription of 12% mass fraction hyaluronic acid, 12% mass fraction oxidized hyaluronic acid and 2.5% propargyl cysteine is 1min. The optimal formula selected was 12% by mass of hyaluronic acid, 12% by mass of oxidized hyaluronic acid, and 2.5% by mass of propargyl cysteine. Figure 5 , the scanning electron micrograph of the gel can be observed.
[0056] Preparation of injectable nanocomposite hydrogels:
[0057] As described in the above preparation method, 12% by mass of hyaluronic acid, 12% by mass of oxidized hyaluronic acid and 2.5% by mass of propargyl cysteine were weighed according to the optimal recipe and dissolved in 1% by mass of sodium hydroxide solution to form a gel solution.
[0058] Weigh sodium hydroxide and gluconolactone in a molar ratio of 1:1 and 2.5% of biomimetic nanoparticles, add them to the gel solution and stir at room temperature for 1 minute to obtain a nanocomposite gel. Figure 5 , the internal structures of the blank gel (left) and the nanocomposite gel (right) can be observed. Figure 6 Good injectable self-healing ability of the gel can be observed.
[0059] Example 6
[0060] In vitro epithelial cell migration in injectable self-healing nanocomposite hydrogels
[0061] 5 × 10 4Hacat cells were cultured in MEM medium + 20% FBS and 1% PS in a cell culture incubator with 5% CO2. After 12 hours, 100 ng / ml LPS was given to stimulate the epithelial cells for 4 hours. Subsequently, a wound was made on the epithelial cells using a 200 μl gun tip, and the floating cell debris was washed away with phosphate buffer solution. The culture medium was discarded and MEM + 2% FBS + 1% PS culture medium was added. At the same time, blank gel (OHG), propargyl cysteine drug-loaded gel (S@OHG), biomimetic quercetin nanoparticle drug-loaded gel (Q@OHG) and propargyl cysteine and biomimetic quercetin nanoparticle double drug-loaded gel (QS@OHG) were added to the culture medium, and photographed and observed under an inverted microscope at 12h, 24h, and 36h. The cell migration rate was calculated according to the formula:
[0062] Migration rate = (initial wound area - timed wound area) / initial wound area × 100%
[0063] Wound healing curve Figure 7 B, Migration rate of wound after 12 hours Figure 7 C.
[0064] Example 7
[0065] In vitro angiogenesis study of injectable self-healing nanocomposite hydrogels
[0066] Matrigel matrix gel was used to test the in vitro tube formation ability of HUVECs cells. 50 μL / well of Matrigel matrix gel was spread in a 96-well plate. HUVECs cells were cultured in a cell culture incubator with 5% CO2 using DMEM medium + 10% FBS + 1% PS. After the cells adhered to the wall, the medium was replaced with DMEM medium + 1% PS to starve the HUVECs cells for 24 hours. Subsequently, 2×10 4 HUVECs cells were placed in a 96-well plate filled with matrix gel. At the same time, blank gel (OHG), propargylcysteine-loaded gel (S@OHG), biomimetic quercetin nanoparticle-loaded gel (Q@OHG) and propargylcysteine and biomimetic quercetin nanoparticle dual-loaded gel (QS@OHG) were added to the cell culture medium and incubated for 6 hours. Representative photos of tube formation were taken by inverted microscope. The actual pictures of in vitro tube formation are shown in Figure 8 A, Statistical analysis of branch points at 6 hours of tube formation. Figure 8 B. The results show that the nanocomposite hydrogel (QS@OHG) of the present invention has a significant angiogenesis-promoting effect.
[0067] Example 8
[0068] Injectable self-healing nanocomposite hydrogel for the treatment of diabetic wounds
[0069] Establishment of diabetic rat model:
[0070] 180-200g SD rats were taken and fasted for 12h after adaptive feeding. 65mg / kg streptozotocin (STZ) was injected intraperitoneally in the fasting state. Blood was collected from the tail vein on the 3rd, 7th and 14th days to measure fasting blood glucose levels. When the blood glucose level was stable at 16.7 mmol / l, the diabetic model was successfully established. Then, 2ml / kg sodium pentobarbital was injected intraperitoneally for anesthesia; after the rats were anesthetized, 4cm on the left and right sides of the spine were used as the modeling area, and the hair was sheared and depilated. The skin in the modeling area was fully excised with surgical scissors, with a diameter of 8mm, deep to the subcutaneous layer, without damaging the muscle layer, and the steel ring was sutured around the wound with 2-0 surgical sutures, and bandaged with bandages and gauze to make a full-thickness diabetic skin defect model.
[0071] Rats were randomly divided into 6 groups, each with 6 rats. After the diabetic model was established, they were randomly divided into diabetic group (Control), quercetin biomimetic nanoparticle group (NM-NP), blank gel group (OHG), propargylcysteine drug-loaded gel group (S@OHG), biomimetic quercetin nanoparticle drug-loaded gel group (Q@OHG) and propargylcysteine and biomimetic quercetin nanoparticle dual drug-loaded gel group (QS@OHG). Nanoparticles were dripped and gels were replaced on the 3rd, 7th, 10th and 12th days in each group.
[0072] Comparison of wound healing
[0073] like Fig. 9 As shown in AB, on the 3rd day, the drug-treated gel groups were higher than the model group, nano-group and blank gel group, showing the effect of promoting wound healing. At the same time, the propargylcysteine and biomimetic quercetin nanoparticles dual-drug gel group (QS@OHG) was significantly higher than the propargylcysteine drug-loaded gel group (S@OHG) and the biomimetic quercetin nanoparticles drug-loaded gel group (Q@OHG). On the 12th day, the biomimetic quercetin nanoparticles drug-loaded gel group (Q@OHG) and the propargylcysteine and biomimetic quercetin nanoparticles dual-drug gel group were significantly higher than the model group (QS@OHG), nano-group (NM-NP), blank gel group (OHG) and propargylcysteine drug-loaded gel group (S@OHG). In summary, the propargylcysteine and biomimetic quercetin nanoparticle dual drug-loaded gel group (QS@OHG) significantly improved the ability of diabetic wound healing, and the effect was better than other groups. It is an ideal dressing for promoting diabetic wound healing.
[0074] It should be noted that the embodiments described herein are only partial embodiments of the present invention, rather than all implementations of the present invention, and the embodiments are only exemplary, and their role is only to provide a more intuitive and clear way to understand the content of the present invention, rather than to limit the technical solutions described in the present invention. Without departing from the concept of the present invention, all other implementation methods that can be thought of by ordinary technicians in this field without creative work, and other simple replacements and various changes to the technical solutions of the present invention, all belong to the protection scope of the present invention.
Claims
1. An injectable nanocomposite hydrogel, characterized in that: The injectable self-healing nanocomposite hydrogel is composed of hyaluronic acid, oxidized hyaluronic acid and propargyl cysteine encapsulating quercetin biomimetic nanoparticles. The hyaluronic acid, oxidized hyaluronic acid and propargyl cysteine are dissolved in a sodium hydroxide solution by physical blending to form a hydrogel solution. At the same time, gluconolactone and biomimetic nanoparticles are added and physically blended at room temperature to form a nanocomposite hydrogel. The encapsulated quercetin biomimetic nanoparticles are composed of quercetin encapsulated nanoparticles and activated neutrophils. The nanoparticles are prepared by a solvent evaporation method. The nanoparticles and neutrophils are encapsulated in an outer membrane by an ultrasonic probe.
2. The injectable nanocomposite hydrogel according to claim 1, characterized in that: The nanoparticles and the neutrophil cell membrane are fused by an ultrasonic probe, and the mass ratio is 5:1-1:5, and the mass fraction is 0.5%-2%; the mass fraction of the hyaluronic acid is 8%-24%, the mass fraction of the oxidized hyaluronic acid is 8%-12%, the mass fraction of the propargyl cysteine is 0.5%-5%, and the drug is a hydrophilic hydrogen sulfide donor.
3. The injectable nanocomposite hydrogel according to claim 1, characterized in that: Hyaluronic acid, oxidized hyaluronic acid and propargylcysteine were dissolved in a 1% by mass sodium hydroxide solution by physical blending.
4. The injectable nanocomposite hydrogel according to claim 1, characterized in that: Neutrophils were obtained by DMSO-induced differentiation of the HL-60 cell line. After further inflammatory stimulation, the cells were activated and overexpressed inflammatory cytokine receptors and related adhesion factors on their surfaces. The neutrophil membrane was obtained by mechanical grinding and differential centrifugation extraction, and cell membrane vesicles were obtained by ultrasonic treatment.
5. The injectable nanocomposite hydrogel according to claim 4, characterized in that: Related adhesion factors include CD11b, TNF-α, IL-1β, TLR-1, and TLR-2 membrane proteins.
6. The injectable nanocomposite hydrogel according to claim 1, characterized in that: The injectable self-healing nanocomposite hydrogel is prepared from raw materials in the following weight ratio: the mass fraction of the hyaluronic acid is 12%; the mass fraction of the oxidized hyaluronic acid is 12%; the drug used is propargyl cysteine, and the mass fraction of the drug is 2.5%; the encapsulated quercetin bionic nanoparticles are PLGA bionic nanoparticles encapsulating quercetin, and the mass fraction of the encapsulated quercetin bionic nanoparticles is 2.5%.
7. A method for preparing an injectable self-healing nanocomposite hydrogel, characterized in that: The injectable self-healing nanocomposite hydrogel was obtained by the following steps: Preparation of quercetin-encapsulated bionic nanoparticles: the quercetin-encapsulated bionic nanoparticles are composed of quercetin-encapsulated nanoparticles and activated neutrophils, the nanoparticles are prepared by a solvent evaporation method, and the nanoparticles and neutrophils are encapsulated in an outer membrane by an ultrasonic probe; the prescribed amount of PLGA and quercetin are weighed, dissolved in an organic solvent, the organic solvent is added dropwise into a 10% polyvinyl alcohol aqueous solution, the emulsion is placed under a probe ultrasonic time and frequency, and placed in a fume hood to remove the organic solvent, and then the solution is centrifuged at a speed of 15 to 30 minutes to obtain drug-loaded nanoparticles, and then the residual polyvinyl alcohol and free drugs are washed away under the same centrifugal conditions to obtain encapsulated quercetin bionic nanoparticles; Preparation of injectable self-healing nanocomposite hydrogel: Step 1, dissolving 8% to 24% hyaluronic acid and 8% to 12% oxidized hyaluronic acid in 1% wt sodium hydroxide solution to prepare a mixed hyaluronic acid and oxidized hyaluronic acid solution with a mass fraction of 16% to 36%, and dissolving 0.5% to 5% propargyl cysteine in the hyaluronic acid and oxidized hyaluronic acid solution to form a drug-loaded gel solution; Step 2: adding gluconolactone to the gel liquid, and simultaneously adding 0.5% to 5% by mass of biomimetic nanoparticles, stirring at room temperature, reacting for 30 seconds to 1 minute to obtain an injectable self-healing nanocomposite hydrogel.
8. The method for preparing the injectable self-healing nanocomposite hydrogel according to claim 7, characterized in that: The mass fraction of the hyaluronic acid is 12%, the mass fraction of the oxidized hyaluronic acid is 12%, the drug used is propargyl cysteine, and the mass fraction of the drug is 2.5%; the nanoparticles are PLGA bionic nanoparticles encapsulating quercetin, and the mass fraction of the nanoparticles is 2.5%; the average particle size of the nanoparticles is 150-220nm, and the size of the nanoparticles encapsulating the neutrophil membrane is 170-240nm; the molecular weight of hyaluronic acid and oxidized hyaluronic acid is 800,000-150,0000Da; the mass fraction of the drug-loaded nanoparticles and the drug is 0.5-5%.
9. The method for preparing the injectable self-healing nanocomposite hydrogel according to claim 7, characterized in that: The polymer for preparing the quercetin biomimetic nanoparticles encapsulating is PLGA, the weight ratio of PLGA is 75% lactic acid and 25% glycolic acid, and the molecular weight is 44,000-100,000Da; the organic solvent is a mixture of dichloromethane and acetone; the ratio of the organic solvent to the water solvent is 1:2-1:9, and the frequency of the ultrasonic probe is 130w, 60s-200s.
10. Application of injectable self-healing nanocomposite hydrogel: characterized by: Injectable self-healing nanocomposite hydrogels are used in the preparation of drugs for treating diabetic wounds.